Performance of self-compacting concrete incorporating palm oil fuel ash and egg shell powder as partial cement replacement - Kamaruddin, Mohamad Sufian (2020)
Self-compacting concrete (SCC), is an innovative concrete that uses less aggregates, but high content of cement compared to normal concrete. It is able to flow by itself and does not require compaction. Therefore, raw materials and natural resources are required in large quantities for SCC production. In order, to minimize the usage of the cement in the SCC, the use of agricultural wastes such as palm oil fuel ash (POFA) and eggshell powder (ESP) as partial cement replacement materials for an alternative preventive solution is suggested. This experimental work was conducted to study the potential combined utilization of POFA and ESP as partial cement replacement in SCC. The amount of POFA content ranged between 0% to 15% while ESP varied from 0% to 5% by weight of cement. A total of 90 cubes, 30 cylinders and 30 prisms were prepared for determining compressive, tensile and flexural strength of SCC repectively, while 30 cylinders were additionally prepared to determine modulus of elasticity and Poisson ratio. The physical, chemical, mechanical and microstructural properties were determined, in which it was observed that POFA had high silicon dioxide (62.1%) compared to ESP which had high percentage of calcium oxide (93.4%). Furthermore, based on the results, it was observed that the combined utilization of POFA and ESP enhanced the pozzolanic activity, thus, developing additional calcium silicate hydride (C-S-H) gels which are responsible for the gain in strength. The combined utilization of POFA and ESP as a cement replacement in SCC had good effect on the compressive and tensile strengths. It was found that 5% POFA and 2.5% ESP was an optimum mix to be used in SCC with 28 days of curing which had the compressive strength of 9.66% higher than the control sample achieved.